Oscillation and Asymptotic Behavior of a Three-Dimensional Half-Linear System of Third-Order of Neutral Type - Naeif , Ahmed Abdulhasan; Mohamad, Hussain Ali (Iraqi Journal of Science, 2024)
In this paper, the oscillatory properties and asymptotic behaviour of a third-order three-dimensional neutral system are discussed. Some sufficient conditions are obtained to ensure that all bounded positive solutions of the system are oscillatory or non-oscillatory. On the other hand, the non-oscillatory solutions either converge or diverge when goes to infinity. A special technique is adopted to include all possible cases. The obtained results include illustrative examples.